(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article explores the consequences of Parkinsonism, including motor and non-motor symptoms, functional decline, and the challenges people face. In addition, he explores modern treatments such as medications, deep brain stimulation, physical therapy and lifestyle changes that have revolutionized the treatment of Parkinsonism. By understanding the complexities of Parkinsonism and advances in treatment, people and caregivers can better understand the disease and hope for improved outcomes.